Culture, Privacy Conception and Privacy Concern: Evidence from Europe before PRISM - Nessrine Omrani; Nicolas Soulié (International Telecommunications Society (ITS), 2017)
This article analyses individuals' online privacy concerns between cultural country groups. We use a dataset of more than 14 000 Internet users collected by the European Union in 2010 in 26 EU countries. We use a probit model to examine the variables associated with the probability of being concerned about privacy, in order to draw policy and regulatory implications. The results show that women and poor people are more concerned than their counterparts. People who often use Internet are not privacy concerned. Privacy concerned people are those who have heard bad privacy experience in the media, through word of mouth or have acquaintance who have bad privacy experience. Trusting Internet company leads to no privacy concern. Individuals in hierarchical and competitive countries are privacy concerned and those in countries characterized by equality, cooperation, and favorable for change are not privacy concerned. And finally, having a large view of information considered as personal leads to be privacy concerned.
Keywords: 330